Impact of offending vessel location on lateral spread response variations in hemifacial spasm patients - Ding, Feiyu; Li, Pan; Zuo, Xiaozhou; Xiao, Yong; Wang, Dong; Liu, Yong; Zou, Yuanjie (Frontiers in Neurology, 2025)
ObjectiveThis study aims to investigate the impact of the offending vessel’s compression location on intraoperative lateral spread response (LSR) waveform parameters during microvascular decompression (MVD) for hemifacial spasm (HFS). Additionally, the study evaluates the clinical significance of LSR variations in intraoperative electrophysiological monitoring.MethodsA retrospective analysis was conducted on 72 patients with HFS who underwent MVD at Nanjing Brain Hospital between September 2021 and September 2023. Patients were categorized into two groups based on the compression site of the offending vessel on the facial nerve: the transitional zone (TZ) group and the attached segment (AS) group. General clinical characteristics, intraoperative LSR parameters, and postoperative outcomes were compared between groups. Statistical analyses focused on LSR latency, amplitude, and duration, as well as the patterns of LSR disappearance and postoperative complications.ResultsThe TZ group comprised 31 patients, while the AS group included 41. No significant differences were observed in baseline characteristics between groups. Intraoperative monitoring revealed that LSR disappearance was more frequently incomplete in the TZ group (11.1%) than in the AS group (p < 0.05). LSR latency was significantly longer in the AS group (p < 0.001), while the amplitude in the orbicularis oculi muscle was lower in the TZ group (p < 0.001). Additionally, LSR duration (T2) in the orbicularis oris (p < 0.05) and mentalis muscles (p < 0.01) was longer in the AS group, though the amplitude differences were not statistically significant. Postoperative outcomes showed no significant difference in effectiveness between the groups (AS: 92.7% vs. TZ: 93.5%, p = 0.882). Complications, such as facial palsy and hoarseness, were slightly more common in the AS group, whereas hearing loss and ataxia were more frequent in the TZ group. However, none of these differences reached statistical significance.ConclusionThe compression location of the offending vessel significantly influences LSR parameters, with longer latency and prolonged duration observed in the AS group. Despite these variations, postoperative outcomes and complications were comparable between groups. These findings highlight the importance of considering the compression location during MVD and the potential value of LSR monitoring in guiding surgical decision-making.